2021
DOI: 10.1097/mao.0000000000003342
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Hearing Preservation and Speech Perception Performance Outcomes With the Slim Modiolar Electrode

Abstract: Objective: Describe audiologic outcomes in hearing preservation (HP) cochlear implant candidates using a slim modiolar electrode (SME). Study Design: Retrospective. Setting: Tertiary referral center. Patients: Two hundred three adult cochlear implant patients with preoperative low-frequency pure-tone average (LFPTA) 80 dB HL that received the SME. Intervention: Implantation with a SME electrode. Main Outcome Measures: Primary outcome was postoperative HP, defined as LFPTA 80 dB HL. HP status was analyzed at ''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
(70 reference statements)
1
24
0
Order By: Relevance
“…With a full electrode insertion and no RT-ECochG feedback, the new SLWE demonstrated a significantly worse LFPTA average shift at 3-months postoperatively when compared with other recent slim perimodiolar electrodes and lateral wall electrodes (38)(39)(40). Our previous experience with the slim perimodiolar electrode (CI532/CI632) (41) shows a LFPTA threshold shift of 19.5 AE 12.3 dB HL at 3-months postoperatively with a HP rate of 61.1% (as compared with a 57.5 AE 25.6 dB HL threshold shift and HP rate of 23.3% with the SLWE without active feedback). The experience in this study suggests that, without RT-ECochG, rates of hearing preservation are worse, as well as LFPTA threshold shifts, and speech-perception performance.…”
Section: Discussionmentioning
confidence: 82%
“…With a full electrode insertion and no RT-ECochG feedback, the new SLWE demonstrated a significantly worse LFPTA average shift at 3-months postoperatively when compared with other recent slim perimodiolar electrodes and lateral wall electrodes (38)(39)(40). Our previous experience with the slim perimodiolar electrode (CI532/CI632) (41) shows a LFPTA threshold shift of 19.5 AE 12.3 dB HL at 3-months postoperatively with a HP rate of 61.1% (as compared with a 57.5 AE 25.6 dB HL threshold shift and HP rate of 23.3% with the SLWE without active feedback). The experience in this study suggests that, without RT-ECochG, rates of hearing preservation are worse, as well as LFPTA threshold shifts, and speech-perception performance.…”
Section: Discussionmentioning
confidence: 82%
“…The position and orientation of the sheath inside the ST plays a central role in the insertion of the slim modiolar electrode. Whereas optimal sheath position almost guarantees a perfect electrode insertion, incorrect placement of the sheath can result in electrode translocation and electrode tip fold-over [13][14][15][16][17][18][19][20][21] . Both of these complications pose a high risk for structural damage leading to residual hearing loss and suboptimal CI performance [13][14][15][16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…This 5.5 mm long sheath acts as a guide catheter for insertion through the round window membrane or through a surgically drilled opening in the cochlear bone (a cochleostomy), and the entire length of the sheath is inserted into the ST. Once the sheath is inserted into its final position, the electrode array is pushed out through the sheath, whereby its pre-coiled shape naturally follows the inner curvature of the cochlea. Clinical studies showed that with this design, electrode translocations could be reduced to less than 6.6% 13 20 . The translocations that did occur typically happened in the proximal part of the cochlea, along the insertion trajectory of the sheath 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently minimally invasive surgery and delicate electrode array design have allowed hearing preservation in CI surgery, although the hearing preservation rate differs according to studies [95][96][97]. A trend toward better hearing preservation in genetically diagnosed cochlear A c c e p t e d A r t i c l e implantees have been proposed, especially in patients carrying pathogenic variants of genes specifically expressed in the stereocilia of hair cells [92,98].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%